2019
DOI: 10.1111/gbb.12604
|View full text |Cite
|
Sign up to set email alerts
|

Novel behavioural characteristics of the superoxide dismutase 1 G93A (SOD1G93A) mouse model of amyotrophic lateral sclerosis include sex‐dependent phenotypes

Abstract: Amyotrophic lateral sclerosis (ALS) involves the rapid degeneration of upper and lower motor neurons leading to weakening and paralysis of voluntary movements. Mutations in copper‐zinc superoxide dismutase 1 (SOD1) are a known genetic cause of ALS, and the SOD1 G93A mouse has been used extensively to investigate molecular mechanisms in ALS. In recent years, evidence suggests that ALS and frontotemporal dementia form a spectrum disorder ranging from motor to cognitive dysfunctions. Thus, we tested male and fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 76 publications
3
22
0
Order By: Relevance
“…The current study found that the overall ability to acquire the CB and reversal CB task (i.e., the ability to learn the position of a food reward within the overall training period) was not affected in 12-month-old APPxPS1 mice and that CBD did not affect spatial learning when considering intermediateterm and reference memory. Investigating CB learning in that detail has only recently been described (Kreilaus et al, 2019); thus, this is the first study to identify that the intermediate-term and long-term retention learning memory of 12-month-old APPxPS1 female mice appear intact. Interestingly, spatial learning and reversal spatial learning of the APPxPS1 mice were delayed by one day when considering performance across three daily trials compared to WT mice on a day-to-day basis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current study found that the overall ability to acquire the CB and reversal CB task (i.e., the ability to learn the position of a food reward within the overall training period) was not affected in 12-month-old APPxPS1 mice and that CBD did not affect spatial learning when considering intermediateterm and reference memory. Investigating CB learning in that detail has only recently been described (Kreilaus et al, 2019); thus, this is the first study to identify that the intermediate-term and long-term retention learning memory of 12-month-old APPxPS1 female mice appear intact. Interestingly, spatial learning and reversal spatial learning of the APPxPS1 mice were delayed by one day when considering performance across three daily trials compared to WT mice on a day-to-day basis.…”
Section: Discussionmentioning
confidence: 99%
“…An accelerating rotarod paradigm was used to measure the motor coordination and balance of the test mice ( Brooks and Dunnett, 2009 ). Training and testing were carried out as described previously ( Kreilaus et al, 2019 ), but with two consecutive test days with two trials per day. The mean of the four trials was considered for analysis, as was the worst-performing trial.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…USVs also play a key role in pup‐mother communication, and Nolan et al find that male and female Fmr1 (a gene linked to fragile X syndrome) knockout or heterozygous mice exhibit discrete patterns of altered vocalizations compared with their wildtype, same‐sex littermates. Finally, in a mutant mouse model of amyotrophic lateral sclerosis (ALS), Kreilaus et al report that prior to the onset of expected motor deficits, mutant males, but not females exhibited reduced sociability, pointing to a potential sex‐specific early marker of the disease.…”
mentioning
confidence: 99%